Neurological Manifestation of COVID-19: A Literature Review - Arash Azhideh (Shahid Beheshti University of Medical Sciences, 2020)
In December 2019, the coronavirus ((COVID-19) outbreak related to severe acute respiratory syndrome (SARS-CoV2) originated in China and expanded exponentially as a public health pandemic to over 200 countries. Over 8 million validated cases and approximately 800000 deaths. The main type is cardiac and respiratory but neurological symptoms are further mentioned as case series and case records in the research. The most frequent manifestations have been reported to include dizziness and headache followed by delirium and encephalopathy. Gillian barre syndrome, acute transversal myelitis, cerebrovascular accident, and encephalitis are among the complications noted. The most prominent occurrence at the periphery was hyposmia. This is also known that neurological demonstrations will also lead to regular features such as cough and fever, which evolve in these cases later on normal manifestations. For the timely diagnosis and separation of cases, therefore, a great suspicion guide is needed to arrest spread in neurology departments. This research provides a narrative study of COVID-19’s neurological symptoms and complexities. Our goal is to inform the neurologists and clinicians who work amidst potential COVID-19 patients regarding potential neurological symptoms, and likely neurological problems arising from the aforementioned new virus.